Matching the Color Difference Between Asphalt Mixture and Cement Grouting Paste Used in Semi-flexible Pavement - Haibin, Deng; Shungui, Wang; Yingchen, Liu; Yinfei, Du; Tangzhong, Wei (Frontiers in Materials, 2022)
In order to match the color difference between black asphalt mixture and light-color cement grouting paste in semi-flexible pavement, carbon black (CB) with four mass ratios (i.e., 2%, 4%, 6% and 8%) was incorporated in a rapid-hardening cement grouting paste. The fluidity, color difference, spectrum reflectance, thermal conductivity and flexural and compressive strength of the above cement pastes were experimentally investigated. The results show that the mass ratios of component in cement paste could ensure the good fluidity of cement grouting paste. Three parameters such as thermal conductivity, flexural and compressive strength all reduced, compared with control paste. However, the compressive strength of the 8% CB paste was still much higher than that of asphalt mixture. According to the color difference results, CB significantly improved the black color of cement paste, of which the black color of asphalt mixture was between that of 6% and 8% CB cement paste. Besides, the spectrum reflectance of all the pastes reduced. Especially, the average reflectance of 2% CB cement paste was 51.7% lower than that of control paste. The findings in this study are expected to help design more advanced cement grouting materials to improve the optical and mechanical performances of semi-flexible asphalt pavement.